Analisis Bibliometrik terhadap Perkembangan Riset Internasional mengenai Implementasi Montessori dalam Pendidikan Inklusi - Rita Anisaturrizqi; Prima Cristi Crismono; Anis Rofi Hidayah (Program Studi Pendidikan Guru PAUD FKIP Universitas Mulawarman, 2025)
Abstract In an era of increasingly inclusive and future-oriented education, research on the development of Montessori approaches and inclusive education has become highly relevant and important. This research aims to analyze the development of research on Montessori education and inclusive education globally, including the integration of special needs such as dementia care. The method used is a descriptive quantitative approach with bibliometric analysis through data from the Scopus database, using related keywords such as